FATAL COMPLICATION OF RECTAL WASHING: A CASE REPORT OF HYPOKALEMIA AND CARDIAC ARREST IN ADVANCED RECTOSIGMOID CANCER - Lukman, Stephen; Sudartana, I Ketut (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Rectal washing is a routine procedure in bowel preparation but may cause complications, especially in high-risk patients. This report discusses a case of fatal complications following rectal washing in a patient with a malignant rectosigmoid tumor and comorbidities, emphasizing the potential risks of hypokalemia and cardiac instability. Method. A case study was conducted on a 65-year-old male with chronic heart failure and suspected rectosigmoid malignancy, who underwent colonoscopy at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, Bali. Comprehensive clinical data were obtained, including detailed medical history, physical examination, laboratory testing, imaging studies (ultrasound and CT scan), and colonoscopy with biopsy. Management adhered to established protocols for atrial fibrillation with rapid ventricular response, chronic heart failure, partial bowel obstruction, and suspected metastatic rectosigmoid carcinoma. The patient's condition was closely monitored through continuous assessment of vital signs, clinical progression, and follow-up diagnostics. Result & Analysis. The case highlights the interplay of rectal washing, electrolyte imbalance (suspected hypokalemia), and cardiac arrhythmia in a high-risk patient. Contributing factors such as metastatic burden and comorbidities compounded the fatal outcome. Discussion. This case underscores the need for vigilant monitoring and tailored bowel preparation strategies in patients with significant comorbidities to mitigate life-threatening complications.